Review of 1971/02/18 Concert at Town Hall, Birmingham. Concert of works by Messiaen and Shostakovitch given by the City of Birmingham Symphony Orchestra and the Ladies of the Birmingham School of Music Choir, conducted by Louis Fremaux. - Lane, Philip (Contact: A Journal for Contemporary Music (1971-1990), 1971)
-